PELATIHAN PENERAPAN MODEL INKUIRI MENGGUNAKAN ALAT PERAGA PADA PEMBELAJARAN MATEMATIKA - Karjiyati, Viktoria; Supriatna, Irfan; Agusdianita, Neza (Universitas Muhammadiyah Tapanuli Selatan, 2022)
SDIT Insan Mulia is one of the Islamic-based private elementary schools in Bengkulu City. This elementary school is located on Jalan Halmahera, Surabaya Village, Bengkulu City. This activity aims to improve the knowledge and skills of teachers regarding the inquiry learning model using teaching aids that can help students understand mathematics learning material more easily. The method used in this PKM activity is training and mentoring. The training was conducted to increase the knowledge and insight of teachers about the nature of learning mathematics in elementary schools, the characteristics of mathematical concepts, cognitive development of elementary school children, teaching aids for mathematics subjects and inquiry learning models in mathematics learning. The training will produce lesson plans with an inquiry model using mathematical teaching aids. Furthermore, the target teacher is asked to carry out the learning or lesson plans he made. The Lecturer Team will provide continuous assistance to direct, guide, and assist the target teacher when preparing lesson plans, making teaching aids and carrying out learning up to evaluating. To evaluate the activities, interview and observation techniques were used. This activity has been carried out up to training and mentoring for teachers in making and implementing learning tools for class IV SDIT Insan Mulia.